Pattern of infectious diseases in acute leukemia during induction therapy - Sri Rezeki Harun; Debbie Latupeirissa; Taralan Tambunan (Indonesian Pediatric Society, 1999)
An prospective study was conducted to determine risk factors and pattem of infectious diseases in acute leukemia during induction therapy. The study subjects were all new acute leukemia patients of J month to 17 years old diagnosed between August 1, 1997 and July 31, 1998 in theÂ Department of Child Heallb, Cipto Mangunkusumo Hospital, Jakarta. Subjects were categorized into Group with and without infection. Of the 39 subjects studied (23 boys and 16 girls), 22 subjects were infected (10 boys and 12 girl ). Most of the subjects were 1-4 year-old age group and 14 subjects of that group were infected. lt was found that there wereÂ relationships between incidence of infection with leukocyte count below 5000/ÂµL (p=0.02), neutrophil count below 1x109/L (p=0.01), and evidence of presumptive site of infection (p=0.0005). Children under 5 years old, sex, ANLL type, malnutrition, or neutropenia of more than 2 weeks had no relationships with incidence of infection. Besides fever, pattem of infection diseases in acute leukemia patients during induction therapy, were only 36% and 38% of subjects had clinical manifestations evidence andmicrobiologically documented, respectively. Most of the laboratory findings were leukopenia or neutropenia, while serum aminotransferase was normal in both groups. Serum CRP serum was devated in those with infection. All of the isolated bacteriae were Gram-negative; 52.4% of infected subjects had responded to empirical therapy, and 72.7% of the antibiotics used was sefotaxime.